티타늄 음극기지의 양극산화 전해질 농도에 따른 구리전착층 표면 및 전기적 특성에 미치는 효과 - 이만형; Man Hyung Lee; 박은광; Eun Kwang Park; 우태규; Tae Gyu Woo; 박일송; Il Song Park; 윤영민; Young Min Yoon; 설경원; Kyeong Won Seol (대한금속·재료학회지, 46(11), 2008)
Recently, the requirement for the ultra thin copper foil increases with smaller and miniaturized electronic components. Therefore, it is important to examine the surface state of substrate depending on the processing parameter during the anodic oxidation. This study investigated the effect of the various electrolyte concentrations on anodizing of titanium anode prior to copper electrodeposition. Different surface morphology of anodized titanium was obtained at different electrolytic concentration 0.5 M to 3.0 M. In addition, the effect that the surfaces and the electrical characteristics on the electrodeposited copper layer was observed. In this study, surface anodized in the group containing 0.5M H2SO4 shows more uniform copper crystals with low surface roughness. the surface roughness and sheet resistance for 0.5M H2SO4 group were 1.353 μm and 0.104 mΩ/sq, respectively.